Income taxation, tuition subsidies, and choice of occupation : implications for production efficiency - Geir Haakon Bjertnæs (Center for Economic Studies and ifo Institute (CESifo), 2005)
The desirability for production efficiency is re-examined in this study, where agents choose occupation based on lifetime income net of tuition costs. Efficient revenue raising implies that the government should trade off efficiency in production for efficiency in intertemporal consumption, as capital income is taxed in optimum. The subsequent wage difference between high- and low-skilled occupations is increased compared to a production efficient outcome, which is in contrast to previous results in the literature.
Keywords: H21; H24; 330; optimal income taxation; subsidies for tuition; skill formation; production efficiency; Einkommensteuer; Optimale Besteuerung; Berufswahl; Bildungsertrag; Studienfinanzierung; Technische Effizienz; Zeitpräferenz; Theorie